AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DI KABUPATEN JEMBER - Febri Arifiyanto, Dwi; Kurrohman, Taufik (Jurnal Riset Akuntansi dan Keuangan, 2014)
This research focuses on the application of the system of accountability of managing the allocation of funds is a village in the District of Jember Regency Umbulsari. In order to know how the implementation of the accountability system of managing the allocation of funds is a village in the District of Jember Regency Umbulsari starting from the stage of planning, execution and accountability. This research is expected to be beneficial to Jember Regency Government in particular sub district of Umbulsari in an effort improve accountability of the management of the allocation of funds for the village. The study is done at villages in sub-districts umbulsari. As informants in this study certainly people who are directly involved and understand and can provide information about managing the allocation of funds for villages, namely the Government of the village as the village of peleksana and team empowerment Institute Executive team as the village community activities. The results of this research show that the planning and implementation of activities of the village Fund Allocations already indicates that management accountable and transparent. From the side of accountability both in terms of physical as well as the Administration is already showing the implementation of accountable and transparent.